Evaluation of the GlideScope Direct: A New Video Laryngoscope for Teaching Direct Laryngoscopy - Darwin Viernes; Allan J. Goldman; Richard E. Galgon; Aaron M. Joffe (Anesthesiology Research and Practice)
Background. Teaching direct laryngoscopy is limited by the inability of the instructor to simultaneously view the airway with the laryngoscopist. Our primary aim is to report our initial use of the GlideScope Direct, a video-enabled, Macintosh laryngoscope intended primarily as a training tool in direct laryngoscopy. Methods. The GlideScope Direct was made available to anyone who planned on performing direct laryngoscopy as the primary technique for intubation. Novices were those who had performed <30 intubations. Results. The GlideScope Direct was used 123 times as primarily a direct laryngoscope while the instructor viewed the intubation on the monitor. It was highly successful as a direct laryngoscope (93% success). Salvage by indirect laryngoscopy occurred in 7/9 remaining patients without changing equipment. Novices performed 28 intubations (overall success rate of 79%). In 6 patients, the instructor took over and successfully intubated the patient. Instructors used the video images to guide the operator in 16 (57%) of those patients. Seven different instructors supervised the 28 novices, all of who subjectively felt advantaged by having the laryngoscopic view available. Conclusions. The GlideScope Direct functions similarly to a Macintosh laryngoscope and provides the instructor subjective reassurance, while providing the ability to guide the trainee laryngoscopist.